Enhanced mechanical properties in β-Ti alloy aged from recrystallized ultrafine β grains. (October 2020) - Zhang, Bingjie; Chong, Yan; Zheng, Ruixiao; Bai, Yu; Gholizadeh, Reza; Huang, Mingda; Wang, Dong; Sun, Qiaoyan; Wang, Yunzhi; Tsuji, Nobuhiro
Abstract: Ultrafine β grain structures with recrystallized morphologies were fabricated by severe plastic deformation and subsequent annealing in Ti-10Mo-8 V-1Fe-3.5Al alloy. The minimum mean β grain size of 480 nm was obtained for the first time as a recrystallized structure in Ti alloys. Precipitation behavior of α in subsequent aging significantly changed with decreasing the recrystallized β grain size. Both tensile strength and total ductility of the aged Ti-alloy were increased by the β grain refinement. Tensile strength of 1.6 GPa and total elongation of 9.1% were achieved in the aged specimen having the prior β grain size of 480 nm, which was attributed to its finer and more homogeneous precipitated microstructure having a mixture of nanoscale thin-plate α and globular α without side α plates along β grain boundaries. Graphical abstract: Unlabelled Image Highlights: 480 nm grain size of recrystallized β structure could be obtained in β-Ti alloy for the first time. The ultrafine β structure made the precipitation structure of α finer and more uniform significantly. 1.6 GPa tensile strength and 9.1% total elongation could be achieved in the aged material having β grain size of 480 nm. Uniform precipitated structure supprressed crack initiation near β grain boundary.